Global governance. - Marx, Axel; Wouters, Jan, 1964- (International law (Edward Elgar) ;, 2018)
Global governance emerged as a concept more than two decades ago. Despite its relevance to key processes underlying the major public policy questions of our age, the contours of 'global governance' remain contested and elusive. This Research Review seeks to clarify key trends and challenges in global governance by bringing together the leading scholarship on its different forms. The Research Review discusses key issues in relation to global governance institutions: democracy, legitimacy, accountability, fragmentation, effectiveness and dispute settlement.